1985
DOI: 10.1530/acta.0.1080277
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone precursors in spermatic venous blood of normal men and varicocele patients

Abstract: In the present study we determined progesterone (p), 17-OH-progesterone (17-OH-P), androstenedione (\g=D\4), dehydroepiandrosterone (DHEA) and testosterone (T) in spermatic venous blood of 34 varicocele patients and of 13 normal subjects. We also used the DHEA/\g=D\4 ratio as an index of the \ g=D\ 5/ \ g=D\ 4 pathway ratio in testosterone biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Testosterone showed a significant decrease which agrees with the findings of Comhaire and Vermeulen [3], Hudson et al [11] and Ando et al [1]. However, Pirke et al [15] and Pasqualini et al [14] found normal testosterone serum levels in varicocele.…”
Section: Testicular Histopathologic Changessupporting
confidence: 86%
“…Testosterone showed a significant decrease which agrees with the findings of Comhaire and Vermeulen [3], Hudson et al [11] and Ando et al [1]. However, Pirke et al [15] and Pasqualini et al [14] found normal testosterone serum levels in varicocele.…”
Section: Testicular Histopathologic Changessupporting
confidence: 86%
“…T is able to effectively inhibit in vitro-induced apoptosis of human spermatocytes and spermatids, and is thus a germ cell survival factor (1). In the present study, there was nonsignificant difference between serum T levels of varicocele-associated cases and fertile controls obtained from results yielded by different investigators showing reduced serum T levels in males suffering from varicocele that increased after varicocelectomy (28,29). Seminal T levels were significantly decreased in infertile oligoasthenozoospermic cases with varicocele compared with normozoospermic cases with varicocele obtained from similar studies (30,31).…”
Section: Discussioncontrasting
confidence: 48%
“…Ando et al found reduced serum testosterone level in males with varicocele and increase in serum testosterone level after repair of varicocele. [56][57][58][59][60] Swerdloff and Walsh however showed that there was no difference in testosterone level between males with and without varicocele. 61 Increased LH serum levels and an abnormal response to gonadotropin releasing hormone (GnRH) could implicate a compromise of the hypothalamic-pituitary-gonadal axis involved in the control of testosterone level and spermatogenesis; a pattern similar to hypergonadotropic hypogonadism.…”
Section: Endocrine Imbalancementioning
confidence: 96%